An extensive analysis of the African rice genetic diversity through a global genotyping - (:unkn) unknown (My University, 2014)
We present here the first curated collection of wild and cultivated African rice species. For that, we designed specific SNPs and were able to structure these very low diverse species. Oryza glaberrima, the cultivated African rice, is endemic from Africa. This species and its direct ancestor, O. barthii, are valuable tool for improvement of Asian rice O. sativa in terms of abiotic and biotic stress resistance. However, only a few limited studies about the genetic diversity of these species were performed. In the present paper, and for the first time at such extend, we genotyped 279 O. glaberrima, selected both for their impact in current breeding and for their geographical distribution, and 101 O. barthii, chosen based on their geographic origin, using a set of 235 SNPs specifically designed for African rice diversity. Using those data, we were able to structure the individuals from our sample in three populations for O. barthii, related to geography, and two populations in O. glaberrima; these two last populations cannot be linked however to any currently phenotyped trait. Moreover, we were also able to identify misclassification in O. glaberrima as well as in O. barthii and identified new form of O. sativa from the set of African varieties.
Keywords: African Research